Diversidade e estrutura genética de populações suínas locais de no Estado de Pernambuco Brasil - SILVA, Elizabete Cristina da (2010)
In Brazil, naturalized pigs or animals called locally adapted are endangered species due to the overvaluation of exotic pig breeds that have caused loss of genetic diversity in these populations. Thus, this study aimed to characterize diversity and genetic structure of nine pig genetics groups locally adapted: Baé (n=11), Caruncho (n=07), Canastra (n=29), Canastrão (n=09), Mamelado (n=07), Moura (n=18), Nilo (n=16), Piau (n=17) and mongrel (SRD; n=47) and three exotic breeds (Duroc=04, Landrace=21 and Large White=04) with 18 microsatellite markers as well as testing these markers to allocate individuals from a mongrel population and their actual population. It was detected 198 alleles with 18 loci examined in 190 pigs from 12 genetic groups, all of them were polymorphic with PIC (polymorphic information content) ranged from 0.541 (SW72) to 0.933 (S0005). The results of AMOVA showed that 3.2% of total variation came from the difference between genetic groups (P<0.0001) and 3.6% (P<0.0001) between local and commercials pigs. The average alleles and alleles effectives Nea were lower for commercial Duroc breed (3.65 and 3.008) and higher for mongrel populations (8.89 and 4.53) and Canastra (8.61, 4.58) detaching the high genetic diversity of the last ones. The nine local GG showed greater average value for the rates: alleles average number (Nam = 7.22), Nea (4.18), PIC (0.67) and the expected heterozygosis (He = 0.71), while the heterozygosis observed (Ho = 0.60) was lower due to intrapopulation inbreeding (FIS = 0.17). Using the UPGMA method, Landrace breed was grouped with Canastra, Moura, Canastrão, Baé and Caruncho populations. Another group was formed by populations Piau, Mongrel, Nilo and Mamelado, while Large White and Duroc breeds were isolated from the rest. Based on the two populations (K=2) for allocation of mongrel pigs, most (71.8%) individuals SRD was grouped into separate clusters of commercial breeds. Two clusters seem to accordingly describe the distribution of genetic variability found in 12 GG, which showed low level of differentiation, leading to a complex population genetic structure and the 18 loci were effective to allocate mongrel individuals to their actual population.